Assessing Landscape Pattern Relationship with Dengue Incidence in Peninsular Malaysia - Nuramalina Binti Mohamad; Wan Yusryzal Wan Ibrahim; Ahmad Nazri M. Ludin (Geoplanning: Journal of Geomatics and Planning, 2019)
Dengue is the most common urban disease that is most prevalent in tropical areas. WHO 2009 stated that these diseases has grown a public health concern due to the risk of dengue infection that has increased dramatically between 50 and 100 million cases every year. This issue was very corresponded with landscape and environment changes. The objective of this paper is to discuss how landscape patterns in relation to dengue incidence.  Open website; idengue were highly contributed in this study to locate the most risky area for dengue fever incidence at the township level. Geographic information system (GIS) was used to demonstrate the spatial patterns of all dengue cases in Johor Bahru and Geoprocessing was used to measure the boundary of risk according to the distribution of dengue outbreak. After that, to analyze the spatial landscape pattern, satellite images were used.  Spatial descriptive analysis shows non-strata housing, open space, road, planned commercial, strata housing and drainage system network is the most prevalence land use activity for dengue incidence in Iskandar Region. The finding shows the common landscape composition that relates to dengue cases. In conclusion, the future development of land use should be considered on landscape pattern towards rapid urbanization.